Dictionary of the social sciences. - Calhoun, Craig (New York : Oxford University Press, 2002)
Publisher description: Featuring over 1,800 concise definitions of key terms, the Dictionary of the Social Sciences is the most comprehensive, authoritative single-volume work of its kind. With coverage on the vocabularies of anthropology, sociology, political science, economics, human geography, cultural studies, and Marxism, the Dictionary is an integrated, easy-to-use, A-to-Z reference tool. Designed for students and nonspecialists, it examines classic and contemporary scholarship including basic terms, concepts, theories, schools of thought, methodologies, issues, and controversies. As a true dictionary, it also contains concise, jargon-free definitions that explain the rich, sometimes complex language of these increasingly visible fields
Includes bibliographical references
Keywords: Social sciences -- Dictionaries